The Effects of Customer Reviews and Ratings on Purchase Decisions for Wardah Cosmetics Through the Shopee Marketplace - Nadia Muthmainnah; Moh. Aris Pasigai; Syarthini Indrayani (www.amertainstitute.com, 2026)
The rapid growth of digital marketplaces has transformed consumer purchasing behavior, particularly in the cosmetics industry, where online information plays an important role in reducing uncertainty before purchase. This study examines the effects of customer reviews and customer ratings on purchasing decisions for Wardah cosmetics through the Shopee marketplace among students of the Faculty of Economics and Business, Universitas Muhammadiyah Makassar. This study employed a quantitative associative research design. The population comprised Management students of the 2022 cohort who had purchased Wardah cosmetic products through Shopee. A total of 110 respondents were selected using a sampling approach based on the number of questionnaire indicators. Data were collected through a Likert-scale questionnaire and analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, t-test, F-test, and coefficient of determination with SPSS. The findings reveal that customer reviews have a positive but statistically insignificant effect on purchasing decisions, as indicated by a regression coefficient of 0.122, t-value of 1.443, and significance level of 0.152. In contrast, customer ratings have a positive and significant effect, with a coefficient of 1.105, t-value of 9.958, and significance level below 0.001. Simultaneously, customer reviews and customer ratings significantly affect purchasing decisions, with an F-value of 145.289 (p < 0.001). The adjusted R² of 0.726 indicates that 72.6% of purchasing decision variation is explained by both predictors. These findings highlight the dominant role of customer ratings in online cosmetic purchasing decisions.